SECURE AND INCLUSIVE UTILIZATION OF SHARED DATA POTENTIAL WITH MULTI-KEY HOMOMORPHIC ENCRYPTION IN BANKING INDUSTRY - Adang Haryaman; Nyoman Dwika Ayu Amrita; Finny Redjeki (PT. Kreatif Indonesia Satu, 2024)
The use of multi-key homomorphic encryption (MHE) has become an important topic in the modern banking industry to improve data security and support secure information exchange between financial institutions. This technology allows mathematical operations to be performed on encrypted data without the need to decrypt it first, maintaining the confidentiality of sensitive information during the data analysis and processing process. This study discusses the potential impact of the use of MHE on operational efficiency, risk management and financial inclusion in the banking industry. First, MHE delivers advantages in operational efficiency by enabling banks to compute encrypted data, reducing the risk of data leaks and increasing system responsiveness. Second, the technology supports better risk management by facilitating anonymized data analysis, enabling banks to identify risk patterns and trends without compromising individual privacy. Third, MHE supports financial inclusion by enabling the development of more inclusive, anonymous data-based credit assessment models, opening up access to financial services to those previously difficult to reach. However, the widespread adoption of MHE is faced with several challenges, including high computational load and interoperability issues between different technology platforms. Solutions to address these challenges include the development of more efficient encryption algorithms, investment in IT infrastructure that can handle homomorphic workloads, and industry standardization and collaboration to facilitate effective MHE integration across financial institutions. In conclusion, by harnessing the potential of MHE and overcoming existing technical and regulatory challenges, the banking industry can strengthen data security systems, improve operational efficiency, and support financial inclusion in a more responsive and inclusive way.